Relasi Kuasa dalam Tata Kelola Hutan Mangrove di Desa Aeramo Kecamatan Aesesa Kabupaten Nagekeo - Theresia Florentia Usmini; Syahrin Badrin Kamahi; Diana S.A.N Tabun (Jurnal Sadewa : Publikasi Ilmu Pendidikan, pembelajaran dan Ilmu Sosial, 2024)
The aim of this research is to analyze power relations in Mangrove forest governance in Aeramo Village, Aesesa District, Nagekeo Regency. The research method used is descriptive qualitative, namely describing the current state of the object qualitatively using data obtained from research. The data sources used are primary and secondary data sources. Data collection techniques use observation, interviews and documentation methods. The data analysis techniques used are data collection, presentation, reduction and drawing conclusions. The research results show that power relations are seen from 4 (four) interactions, namely, Decisional, Anticipated Reaction, Non Decision Making, and systemic. In decisional interactions it was found that the decision to change land use was made by the community itself who had power over the land covered by mangrove forests. By forming a group to open a pond. Anticipated reaction interactions found that the desire for land clearing was carried out by each management group based on personal encouragement and oriented towards improving the community's economy. The non-decision making interaction of the management has the power in clearing land because they have a certificate and receive direct support from the provincial government. Systemic interactions found that the interest that the management group carried out from the start was to help the community's economy. The Mangrove forest rehabilitation process has been carried out by the Nagekeo Regency environmental service and the Kajumata Farmers Group which was formed to preserve the Mangrove forest in Aeramo Village. Socialization activities regarding the importance of mangrove forests and the opening of environmentally friendly ponds have also been carried out by the Environmental Service and the Fisheries and Maritime Affairs Service.